Keilgezinkte Rahmenecken und Satteldachträger aus Brettsperrholz - Blaß, Hans JoachimFlaig, Marcus (Karlsruher Berichte zum Ingenieurholzbau / Karlsruher Institut für Technologie, Holzbau und Baukonstruktionen, 2015)
The report describes the experimental and analytical research that was carried out for the development of large double pitched beams and three hinged frames made of cross laminated timber. The results are used to derive of design approaches for large finger joints in cross laminated timber.